Cyclodextrin‐supported palladium complex: A highly active and recoverable catalyst for Suzuki–Miyaura cross‐coupling reaction in aqueous medium. (13th September 2016) - Guo, Yafei; Li, Jiuling; Shi, Xiwei; Liu, Yang; Xie, Kai; Liu, Yuqi; Jiang, Yubo; Yang, Bo; Yang, Rui
Abstract : A water‐soluble, cyclodextrin‐supported palladium complex (DACH‐Pd‐β‐CD) catalytic system was designed and synthesized, which can efficiently catalyze Suzuki–Miyaura cross‐coupling reactions between aryl halides and arylboronic acid in water under mild conditions. The catalyst was successfully characterized using the methods of transmission electron microscopy, energy‐dispersive X‐ray spectrometry, X‐ray diffraction, thermogravimetric analysis, and Fourier transform infrared and NMR spectroscopies. Furthermore, the catalyst can be easily separated from the reaction mixture and still maintain high catalytic activity after ten cycles. No leaching of palladium into the reaction solution occurred. The advantages of green solvent (water), short reaction times (2–6 h), low catalyst loading (0.001 mol%), excellent yields (up to 99%) and reusability of the catalyst mean it will have potential applications in green chemical synthesis. Abstract : A water‐soluble, recyclable, macromolecular palladium complex (DACH‐Pd‐β‐CD) catalytic system was developed for Suzuki–Miyaura cross‐coupling reactions between aryl halides and arylboronic acid with the advantages of green solvent (water), short reaction times, low catalyst loading, excellent yields, easy separation from the reaction mixture and still maintaining high catalytic activity after ten cycles and no leaching of Pd into solution, with potential for application in green chemical synthesis.